Identification and Validation of Long Non-Coding RNA LCIIAR as a Biomarker in LUAD - Ren, Wenjun; Yuan, Yixiao; Chen, Xi; Zhai, Haoqing; An, Yin; Tang, Lin; Wang, Juan; Zhang, Dahang; Zhang, Liren; Cheng, Wanli; Wang, Xin; Duan, Lincan; et al. (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related death worldwide. Therapies for lung cancer have relatively poor outcomes and need to be improved. Lung cancer immune cell infiltration associated RNA (LCIIAR) is a long noncoding RNA (lncRNA), which is overexpressed in human cancers. However, the clinical significance and functional role of LCIIAR in Lung Adenocarcinoma remain unclear. Here, we identified a novel long non-coding RNA (ENSG00000256802), termed LCIIAR (lung cancer immune cell infiltration associated lncRNA), up-regulated in lung cancer tissue and cell lines. We show that increase LCIIAR expression correlated with poor clinical stage and adverse clinical outcomes and that could also serve as an independent unfavorable prognostic factor in patients with Lung Adenocarcinima. GSEA analysis demonstrated that LCIIAR is mainly involved in the regulation of the immune response. We uncovered that elevate LCIIAR expression positively correlated with immune infiltration and immune modulator in Lung Adenocarcinoma. More importantly, we confirmed that silencing of LCIIAR expression significantly inhibits the proliferation, and migration abilities of these tumour cells. We also demonstrated that the LCIIAR/hsa-miR184/SLC16A3/CDCP1 network regulates SLC16A3/CDCP1 overexpression in and is associated with poor prognosis in this tumour. Therefore our findings revealed the critical role of LCIIAR in Lung Adenocarcinoma progression, which may also serve as a prognostic biomarker and novel therapeutic target.